Second home tourism present and future. The case of Greece. (International Journal of Scientific Research and Management (IJSRM), 2021)
Second-home tourism is a rapidly growing form of tourism around the world. Being an integral part of rural areas and their history, second homes are an established example of the post-productive consumption of the countryside. Τhe expansion of urbanization and the pressures of the urban way of life, as well as the search for a pleasant climate and clean environment, have contributed particularly to the development of second home tourism globally. This study intends to investigate the present, the future and the impact of second home tourism on destinations, local people and tourists. The development of second home tourism, or tourist home is, undoubtedly, a strongly evolving social phenomenon. Activated by economically developed societies and is linked to income growth, urbanization, the possibility of geographical mobility and the increase of leisure time. This phenomenon operates and intensifies, almost in parallel with tourism. Also, the study investigates the effects of second home tourism in Greece, a very popular destination for international and domestic tourism. The country has been experienced a high growth of second home tourism in the last few years.